Internalising and externalising in early adolescence predict later executive function, not the other way around: a cross-lagged panel analysis. Issue 5 (4th July 2021) - Donati, Georgina; Meaburn, Emma; Dumontheil, Iroise
ABSTRACT: Developmental changes in the brain networks involved in emotion regulation are thought to contribute to vulnerability to mental health problems during adolescence. Executive control is often viewed as allowing top-down regulation of emotional responses. However, while associations between executive control and mental health are commonly observed in both clinical and non-clinical populations, the direction of these associations remains unclear. Low, or immature, cognitive control could limit emotion regulation. Reversely, high emotionality could impede cognitive functioning. The scarcity of longitudinal studies testing for bi-directional effects, particularly in adolescence, has made it difficult to draw conclusions. This study analysed data from 1, 445 participants of a longitudinal cohort in a cross-lagged panel design to understand bi-directional longitudinal associations between executive function and emotional behaviours across adolescence. Executive function was assessed using experimental working memory and inhibitory control tasks, emotional behaviours through parental report of internalising and externalising behaviours. Cross-sectional associations were replicated. Controlling for cross-sectional associations, early executive functions were not found to predict later emotional behaviours. Instead, early emotional behaviours predicted later executive function, with the strongest link observed between early externalising and later working memory. These results suggest that emotional well-being may affect the maturation of executive function during adolescence.